THE RELATIONSHIP OF MECHANICAL OCULAR TRAUMA AND THE BEST-CORRECTED VISUAL ACUITY RESULTS IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Katharina Ratri Benita; Hendrian Dwikoloso Soebagjo; Siprianus Ugroseno Yudho Bintoro (Universitas Airlangga, Surabaya, Indonesia, 2021)
Background: Ocular trauma is an accident caused by a foreign object that affects the eye tissue. Ocular trauma can cause pain and a decrease in the person’s best-corrected visual acuity. Mechanical ocular traumas can cause morphological and functional eye changes that are serious enough to cause blindness. Blindness is often used to describe a severe visual impairment with the remaining visual function. Objective: To determine and to analyze the relationship between mechanical ocular trauma and the best-corrected visual acuity of the patients of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2016-2018. Material and Method: This study was an analytic study with a cross-sectional design. The data were collected using the medical records of the patients of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2016-2018. The population of this study consists of all patients with pure mechanical ocular trauma with a total of 198 subjects. Results: Fisher exact test results showed a value of p=0.054, showing that there was no significant relationship between the best-corrected visual acuity and mechanical ocular trauma. Conclusion: No significant relationship was present between mechanical ocular trauma and the best-corrected visual acuity (BCVA) based on the medical record of patients with ocular trauma in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, Surabaya, in 2016–2018. Most of the patients had BCVA 6/24 - 2 meter counting finger.